Investing in financial research : a decision-making system for better results - Einhorn, Cheryl Strauss (AREA Method Publications., 2019)
"Investing In Financial Research is a guidebook for conducting financial investigations. The book lays out the AREA Method -- a research and decision-making system that uniquely controls for bias, focuses on the incentives of others and expands knowledge while improving judgement -- and applies it to all sorts of financial sleuthing from investment analysis to investigative journalism. The AREA Method provides defined tasks that guide and focus research on a vision of success; a structure that isolates sources, giving insight into their perspectives, biases and incentives; investigative resources, tips and techniques to upgrade research and analysis beyond document-based sources; exercises to foster creativity and originality in thinking; and a sequence and framework that brings disparate pieces of research together to build confidence and conviction about financial decisions"--